ANALYSIS STUDENT’S SPEAKING FLUENCY IN SPEAKING CLASS PERFORMANCE - Aditya - Permana; - - Arjulayana; M. Abduh Al-Manar (Universitas Muhammadiyah Tangerang, 2021)
Speaking skill becomes one of the most fundamental skills in this era; however English learners need to develop their capability to show their language skill through speaking practice. This research aims to investigate students speaking fluency level toward speaking practice. The qualitative descriptive method is used to describe data analysis. The sample of this research is single sample, English language program students at semester 5. The video record towards speaking practice and professional feedback are became the data collection technique. The video records duration is about 10 minutes and during that presentation, researcher tried to analysis based on the vocabulary used, voice, and speech fluency. The result of the research showed that student’s speaking fluency level is still low, and it needed to treat and drill more, could be through watching a YouTube or practice among English learners.